In Vitro Clonal Propagation Of Pomegranate (Punica Granatum L.) Cv. Bhagwa (Applied Biological Research, 2022)
An attempt was made to standardize in vitro clonal propagation of  pomegranate cv. Bhagwa, using nodal segment and shoot tip explants at  e, India. Direct organogenesis of pomegranate was tried in  MS medium with growth regulator combinations viz., benzyl amino purine (BAP), α-naphthalene acetic acid (NAA) and adenine sulphate for in vitro shoot regeneration and indole butyric acid (IBA) for in vitro rooting. Among  the explants evaluated, nodal segments responded better for culture  establishment. Pre-treatment of nodal segments with 0.5% carbendazim for  30 min followed by surface sterilization with 70% ethanol for 30 sec and 0.5%  sodium hypochlorite for 10 min gave highest survival rate (81.7%) with  minimum microbial contamination (13.3%). Phenolic exudation was reduced  by treating explants in antioxidant solution consisting of citric acid (100 mg L-1) and ascorbic acid (150 mg L-1) for 20 min and then cultured on basal MS  medium with polyvinyl pyrrolidone (100 mg L-1) resulted in maximum  survival (98.3%). The earliest shoot evocation response (4.4 days), higher  shoot proliferation (91.7%) and maximum shoot number (4.6) were observed  on basal MS medium with adenine sulphate (40 mg L1). Half strength MS medium supplemented with IBA (1 mg L-1), recorded minimum days to root  initiation (16.9) and maximum rooting percentage (71.7%) with highernumber of roots explant-1(3.7) and lengthier roots (3.93 cm). Rooted plantlets  transferred to hardening media with pot mixture and vermicompost (1:1)  exhibited an ex-vitro survival of 81.7%.
Keywords: Micropropagation; nodal segment; phenolic exudation; pomegranate; rooting; shoot tip